ANALISIS STRATEGI PEMASARAN MELALUI TIKTOK DALAM MEMBANGUN KEPERCAYAAN KONSUMEN TERHADAP PRODUK ARTHA LDT DALAM PERSPEKTIF ETIKA BISNIS SYARIAH DI KABUPATEN SITUBONDO - Yaqin, Ainol; Nurholizah, Wilda (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the marketing strategy implemented by Artha Ldt through the TikTok platform in building consumer trust in their products, as well as to examine the alignment of these strategies with the perspective of Islamic business ethics in Situbondo Regency. TikTok, as one of the rapidly growing social media platforms, offers significant potential for marketing products in a more creative and interactive way. However, in these efforts, companies need to ensure that the marketing approaches used remain in accordance with Islamic principles, such as honesty, transparency, and avoiding fraud. This research uses a qualitative approach with interview methods and content analysis on Artha Ldt’s official TikTok account. The results show that the use of TikTok can be effective in building consumer trust through the delivery of interesting and educational information, as well as more personal interaction. However, several challenges related to the application of Islamic business ethics were also found, such as the potential for promotions that do not align with Islamic principles. Therefore, it is recommended that Artha Ldt pay more attention to Islamic values in every marketing activity to strengthen reputation and consumer trust in the Situbondo market.